Apropriações do método intuitivo de Clakins nas orientações para o ensino de saberes geométricos em revistas pedagógicas brasileiras (1890-1930) - Santos, Joana Kelly Souza dos (2017)
In this text are presented results of a research whose objective was to characterize appropriations about the Calkins’ intuitive method in orientations to teaching geometric knowledge in primary school, present in Brazilian pedagogical journals of period between 1890 and 1930, finded in UFSC’s repository. The contribution came from the use of Chartier (2003) to talk about appropriation, Calkins (1886/1950) about intuitive method and Leme da Silva (2005) about geometric knowledge. The choice to examine the intuitive method from Calkins (1886/1950) can be justified because he was identified as reference in the intuitive method in Brazilian works. After exam, it was identified that the orientations for geometrics knowledge followed two paths: implicit and explicit. In the first case, when the authors used expression such as “lições de coisas” and “Calkins” in the text. In the second case, implicit when it was possible identified the uses of the principles of Calkins. Based on theses paths it was possible to characterize the appropriations from how of the geometric knowledge was related to teaching of lines, points, angles, geometric forms, geometrics figures and geometric solids, with the objective of stimulating the child’s senses, especially from the sight. The authors used principles of Calkins’ intuitive method starting from the dialogue, instigating the students to see the draws or objects and to do sentences about it. The comparison, association and classification were also identified in the treatment of sight education. From this, it was possible to affirm that the author appropriations were related to two uses: use of objects or from the imagination of children. Thus, it was possible to affirm that there was appropriation of Calkins’ intuitive method to teaching geometric knowledge, mainly of the principle of educating of sight, because in the recommendations the observation was highlighted.